KUPASAN ARTIKEL ‘MALAYSIA: THE 2020 PUTSCH FOR MALAY ISLAM SUPREMACY’: CRITICAL APPRAISAL ON MALAYSIA: THE 2020 PUTSCH FOR MALAY ISLAM SUPREMACY’ - Idris, Asmady; Salleh, Asri; Mohd Yaakop, Mohd Rizal (Jurnal Pengajian Melayu (JOMAS), 2021)
Abstract The 2018 General Election (PRU) marked a significant point in the history of Malaysian politics when the major opposition bloc Pakatan Harapan (PH) ended Barisan Nasional (BN) rule of 60 years since gaining independence in 1957. However, the PH government, led by ex-premier Tun Dr Mahathir Mohamad, only lasted 22 months. Accordingly, the sudden collapse of the PH government drew many to offer their respective analyses. James Chin (2020) wrote one of them titled ‘Malaysia: The 2020 Putsch for Malay Islam Supremacy’. He argued that, amongst the many reasons attributable to its sudden collapse, one stood out – the position of Islam and Malay supremacy in Malaysia. Since Malaysia is predominantly a Malay-Muslim country, such a profound claim warrants a thorough response. Thus, this study’s objective is to analyse and offer critiques on Chin’s work based on the three main factors, namely the concept of Malay supremacy, unreadiness of Malays to share power with non-Malays and the position of non-Malays in the top government positions. This study utilised documentary analysis to uplift the discussion to fit the social contract concept and the Federal Constitution and strike a balance between extremist and utopian ideas that best suit Malaysia’s political development reality. The study’s main findings can be narrowed down to show the actual picture of Malaysian political genesis’ uniqueness based on its own identity, which constantly rejuvenates and evolves across time and space. Keywords: General Election 2018, Pakatan Harapan, Islam, Malay supremacy, Malaysian political genesis.